2021
DOI: 10.3389/fpsyg.2021.697358
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Family Sports Attitude on Children’s Sports Participation, Screen Time, and Body Mass Index

Abstract: Background: Children’s physical health is an important resource for a country’s future construction. However, researchers found that the physical fitness of young children around the world has declined during the two decades, from 1992 to 2012. The decline in the physique of young children has caused widespread concern around the world. Children’s main living places are families and kindergartens, so this research explores the impact of family factors on children’s body mass index (BMI) from the perspective of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Parents usually treat the child in a certain way (authoritarian parenting style) in order to gain society's approval (good mother/father/good child). This finding is in line with other studies [54][55][56][57]. Regarding the influence of culture on parents' beliefs, Määttä, et al [58] showed that parents with a low educational background face greater social pressures related to the time their child uses DD, high costs of sports activities, purchasing and using different DD and learning from them at a young age.…”
Section: The Meso Levelsupporting
confidence: 86%
“…Parents usually treat the child in a certain way (authoritarian parenting style) in order to gain society's approval (good mother/father/good child). This finding is in line with other studies [54][55][56][57]. Regarding the influence of culture on parents' beliefs, Määttä, et al [58] showed that parents with a low educational background face greater social pressures related to the time their child uses DD, high costs of sports activities, purchasing and using different DD and learning from them at a young age.…”
Section: The Meso Levelsupporting
confidence: 86%
“…The results obtained in the study, which reveal a low incidence of changes in municipality between the birthplace and place of sporting growth in the early years of play (U-12), can be understood through various dynamics that characterise the initial phases of sports training. In these early stages, the influence of family and community appears to be a preponderant factor [ 34 ]. Decisions about place of residence are influenced by considerations beyond the purely sporting sphere, such as parents’ job opportunities, proximity to relatives, and general quality of life [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study reveals that soccer knowledge, attitude, and practice all have insignificant impacts on individual health, diverging from previous studies. 37 , 38 , 39 , 40 , 41 , 42 Previous studies have shown that individuals with positive attitudes toward sports tend to enjoy better mental health. 40 Jordan argued that favorable sports attitudes lead to sports participation, 43 which in turn enhances individual well-being.…”
Section: Discussionmentioning
confidence: 99%